Association of perinatal depression with behavioral problems of children at 4 years of age: a cohort study - Song-lin SUN; Zhen-zhen XIE; Jin-can LI (Editorial Office of Chinese Journal of Public Health, 2023)
Objective To evaluate the association between perinatal depression at multiple time points and behavioral problems of children at 4 years old. Methods A total of 653 mother-child pairs were included in the study from the Shanghai-Minhang Birth Cohort Study established in 2012. Follow-up interviews were conducted among the mothers at third trimester, childbirth in hospitals and at 6 and 12 months postpartum, 4 years of age of child at homes. Center for Epidemiological Studies-Depression scale was used to assess the depression of the mothers. Behavioral problems of children at 4 years were assessed with the Child Behavior Checklist scale. Log-binomial regression model was adopted to examine the association between perinatal depression and children's behavioral problems. ResultsThe detection rates of depressive symptoms among the mothers were 19.71% (121/614), 10.45% (56/536), 8.65% (45/520), and 4.65% (23/495) at the second and third trimester, 6 and 12 months postpartum, respectively. After adjusting for covariates, maternal depression symptoms at the four time points were associated with an increased risk of children's behavioral problems, and the effects of maternal depression symptom in the second trimester and 12 months postpartum were stronger. Maternal depression in the second trimester was associated with children's emotional reaction, somatic, aggressive behavior, and internal behavior abnormalities, with the relative risk (RR) (95% confidence interval [95% CI]) of 2.01 (1.04 - 3.89), 2.29 (1.20 - 4.34), 1.97 (1.11 - 3.50), and 1.67(1.09 - 2.55), respectively. Besides, maternal depression at 12 months postpartum increased the risk of children's anxiety/depression (RR, 95% CI: 3.27, 1.36 - 7.89), attention problems (2.76, 1.19 - 6.40), withdrawn (2.77, 1.30 - 5.90), aggressive behavior (2.65, 1.24 - 5.66), internal behavior disorders (2.64, 1.48 - 4.71), and external behavior disorders (2.76, 1.42 - 5.34). Similar to the results mentioned above, the maternal depression occurring only during pregnancy or only after childbirth was also associated with behavioral problems of the children.Conclusion Perinatal depression at multiple time points is associated with the increased risk of behavioral problems of children at 4 years of age and the effects of maternal depression in the second trimester and 12 months postpartum are stronger. In addition, maternal depression during pregnancy and postpartum both play independent adverse role on children's neurobehavioral development.